Analysis of an Integrated Photovoltaic Thermal System by Top Surface Natural Circulation of Water - Arefin, Md. Arman (Frontiers in Energy Research, 2019)
The performance of photovoltaic (PV) panel is extremely sensitive to its operating temperature. Most of the energy absorbed by the panel is wasted in the form of heat and provides no value. Integrated photovoltaic thermal system can be a great solution to this problem. In this study, a numerical and experimental work is conducted on hybrid photovoltaic—thermal water heating system with front surface water cooling. First, a numerical analysis is conducted which is capable of describing various thermal parameters affecting the performance of photovoltaic panel and collector. The effect of supplying different mass flow rates of water over the individual photovoltaic and collector system and the overall system are examined thoroughly by experiment. The results of the numerical analysis are found in good agreement with the experimental analysis. Due to active cooling, it was also observed that the overall efficiency of the whole system is approximately five times higher than the efficiency of PV panel alone. Top surface cooling method significantly dropped the panel temperature and increased the panel efficiency by almost 1.5% with an overall system efficiency of around 80% where, PV and collector efficiencies are 16 and 64%, respectively.